Effectiveness and safety of adalimumab in patients with intestinal Behçet’s disease: a real-world prospective observational study in South Korea - Jongwook Yu; Sung Jae Shin; Yune-Jung Park; Hyung Wook Kim; Bo-In Lee; Byong Duk Ye; Geun-Tae Kim; Sung Kook Kim; Joo Sung Kim; Young-Ho Kim; Seonjeong Jeong; Jae Hee Cheon (BMC Gastroenterology, 2023)
Abstract Background Intestinal Behçet’s disease (BD) is characterized by typical gastrointestinal ulcers in patients with BD followed by complications such as bleeding, perforation and fistula. Biologic agents are currently under active investigation to delay the disease course. Various data regarding infliximab are available, but there is relatively lack of data regarding adalimumab. Methods This was a multicenter, real-world prospective observational study to evaluate the effectiveness and safety of adalimumab in intestinal BD. The primary endpoint was disease activity at each follow up, including disease activity index for intestinal Behçet’s disease (DAIBD), serum C-reactive protein (CRP) level, and endoscopic findings. The secondary endpoint was the incidence of adverse drug reactions (ADRs). Results A total of 58 patients were enrolled and 8 of them were excluded. Adverse events were reported in 72.0% of patients with 122 events. ADRs were reported in 24.0% with 28 events. For adverse events, arthralgia was most commonly reported (13.1%: 16/122) and only one experienced critical adverse event (0.82%, 1/122: death due to stroke). On multivariable regression analysis, a longer disease duration was significantly associated with decreased ADRs [Odds ratio 0.976 (0.953–0.999, 95% CI); p = 0.042]. Clinical response rates as assessed by DAIBD were 90.9% at Week 12 and 89.7% at Week 56, respectively. The mean serum CRP level at baseline was significantly decreased after 12 weeks (3.91 ± 4.93 to 1.26 ± 2.03 mg/dL; p = 0.0002). Conclusion Adalimumab was found to be safe and effective in Korean patients with intestinal BD. A longer disease duration was significantly associated with decreased ADRs.